1998
DOI: 10.1097/00002820-199810000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of mothers in five countries whose child died of cancer

Abstract: Although increasing attention is being focused on the emotional aspects of caring for dying children and their families, few research reports concentrate on the experiences of mothers, particularly in different countries. This article describes the findings of an exploratory, descriptive study that investigated the experiences of mothers from five different countries who each had a child die from cancer in the past 6 months. Principal investigators, members of the International Work Group on Death, Dying, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 19 publications
2
22
0
6
Order By: Relevance
“…This is consistent with literature that has associated bonds with positive and negative results for the bereaved (e.g., Boelen, Stroebe, Schut, & Zijerveld, 2006; Davies et al, 1998; Field & Friedrichs, 2004; Field, Nichols, Holen, & Horowitz, 1999; Gamino et al, 2000; Meert et al, 2005; Neimeyer, Baldwin, & Gillies, 2006; Ronen et al, 2009). It is important to point out that mothers reported more comforting effects from continuing bonds than siblings.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with literature that has associated bonds with positive and negative results for the bereaved (e.g., Boelen, Stroebe, Schut, & Zijerveld, 2006; Davies et al, 1998; Field & Friedrichs, 2004; Field, Nichols, Holen, & Horowitz, 1999; Gamino et al, 2000; Meert et al, 2005; Neimeyer, Baldwin, & Gillies, 2006; Ronen et al, 2009). It is important to point out that mothers reported more comforting effects from continuing bonds than siblings.…”
Section: Discussionsupporting
confidence: 93%
“…16 Others have reported that the presence of severe symptoms dictates the location of death, because parents who had wanted their child to die at home will admit their child to the hospital to have better symptom control strategies available. 6,17,18 Our lack of finding such differences in concerning symptoms by diagnosis or location of death may be a factor of our sample size. Analysis of location of death, diagnosis, and most concerning symptoms does merit additional study with a larger group of patients.…”
Section: Discussionmentioning
confidence: 92%
“…In one of the only cross-cultural comparison study, comparing mothers from Canada, Norway, Greece, Hong Kong, and the United States, few differences were found with regard to interpersonal relationship styles or practices done before or after the death of the child (Davies et al, 1998).…”
Section: Reaction To Death and Expressions Of Griefmentioning
confidence: 99%